Beyond HIV microbicides: multipurpose prevention technology products. (October 2014) - Malcolm, RK; Boyd, P; McCoy, CF; Murphy, DJ
Abstract : Multipurpose prevention technologies (MPTs) that aim to simultaneously prevent unintended pregnancy, HIV‐1 infection and other sexually transmitted infections are among the most innovative and complex products currently in development within women's sexual and reproductive health care. In this review article, MPTs are placed within the wider context of combination products, combination drug products and multi‐indication products. The current MPT product landscape is mapped and assessed with reference to existing products for the corresponding single indications, before identifying the gaps in the current MPT product pipeline and highlighting priority products and challenges moving forward.